Adherence to antiretroviral treatment in adults with HIV: knowledge translation in website creation - Marcelo Ribeiro Primeira; Aiodelle dos Santos Machado; Tassiane Ferreira Langendorf; Daniel Gonzalo Eslava Albarracin; Cristiane Cardoso de Paula; Stela Maris de Mello Padoin (Revista Latino-Americana de Enfermagem)
Objective: to create a website to promote adherence to antiretroviral treatment for adults living with the human immunodeficiency virus. Method: methodological research in which the content was developed based on the synthesis of scientific evidence and validated by experts on the subject. The image content was created and linked to the text content for the development of the website. The analysis was performed based on the Content Validity Index by 20 experts recruited using the snowball technique. Results: the content was structured into three axes: self-efficacy, social support and quality of life. Each axis presents a concept, a total of 11 Life Situations with proposals for promoting adherence and 14 images. The overall Content Validity Index obtained a score >0.78. The website is freely accessible. Conclusion: the educational-care technology typified as an informative website was validated by experts on the subject for use by the target population of adults living with the human immunodeficiency virus as a tool for promoting adherence to antiretroviral treatment.